Variation at Glu-1, Glu-3 and Gli-B1 alleles and classification of landraces, old varieties and rust resistant sources in durum wheat - Sakaru, Venkata Sai Prasad (Journal of Cereal Research, 2013)
In durum wheat genotypes, analysis of seed storage protein profiles of 30 genetic stocks was done using Acid and SDS PAGE electrophoresis to find out the existing genetic diversity, and to assess its utility for improvement in grain yield along with quality traits. More alleles were observed at Glu-1 loci i.e., Glu A1 (2*) and Glu B1 (14+15, 7*+8 and new type allele) and band 20 is common in genetic stocks. Genetic stocks contain 12 different pattensat Glu-3 loci, indicating more diversity for this class of proteins. The rust resistance sources do not possess g-45/ Gli-1 alleles, so these lines can be used as donors to introduce disease resistance in the good quality recently released varieties, which are containing g-45/Gli-1 alleles. Six different Gli-B1 alleles were found in land races,rust resistance sources and old released varieties. From hierarchical analysis, it was found that landraces, old released varieties and rust resistance sources are genetically distinct. Significant differences were observed for protein content and sedimentation value between the land races, old released varieties and rust resistant sources.The presence of new LMW –B glutenin and g-gliadin patterns is interesting in rust resistance sources and need to be investigated for their role in pasta making as well as overall technological quality of durum wheat.